The Effect of ESG Disclosure, Audit Quality, Internal Audit, on Company Value - Arlisha Azahra; Hasnawati Hasnawati (CV. Publikasi Indonesia, 2024)
This study aims to examine the presence or absence of the effect of ESG Disclosure, Environmental Disclosure, Social Disclosure, Governance Disclosure, Audit Quality, and Internal Audit on Company Value. The population used in this study is companies listed on the IDX in several non-financial sectors, namely the energy, raw materials, health, industry, and infrastructure sectors in the 2020-2022 period that successively publish sustainability reports, annual reports, and financial statements for the fiscal year December 31. The total population in this study was 346 companies with the number sampled being 45 companies using purposive sampling techniques. The data was analyzed using regression panel data made into two models and processed using E-Views software version 9. The results of this study provide results that in model 1 ESG Disclosure, Audit Quality, Internal Audit partially affect Company Value. The results in model 2 provide results that Environmental Disclosure affects Company Value, Social Disclosure does not affect Company Value, Governance Disclosure does not affect Company Value, Audit Quality affects Company Value, Internal Audit does not affect company value. In model 1 and model 2, the Leverage control variable, ROE has a significant positive influence on Company Value, while Firm Size does not have a positive influence on Company Value